Isolasi Mikroorganisme Limbah Singkong (Manihot Esculenta) Industri Tapioka Menggunakan Media PDA pada Praktikum Mikrobiologi Farmasi - Evelyn Luna Anggraini; Ardi Mustakim (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
Solid waste from the tapioca processing industry, which is based on cassava (Manihot esculenta), is a medium rich in organic matter, particularly starch, that supports the growth of various types of microorganisms, especially fungi and bacteria. This study aims to isolate and observe the morphology of microorganisms from solid waste of cassava from the tapioca industry using Potato Dextrose Agar (PDA) medium in a series of pharmaceutical microbiology practicum. Waste samples were taken from the tapioca processing site, then underwent a serial dilution process and inoculation into PDA medium, which was incubated at 28–30°C for 5 days. The isolation results showed the growth of microorganisms with diverse colony morphologies, which are suspected to originate from the genera Aspergillus, Penicillium, and Rhizopus, based on macroscopic and microscopic characteristics. The presence of these microorganisms indicates the potential utilization of cassava waste as a source of microbial isolates for biotechnological and pharmaceutical applications, such as enzyme production and development of bioactive compounds. This practicum activity also contributes to increasing students' understanding of isolation techniques, microorganism characterization, and their role in biological-based waste management.